Language and culture - Kramsch, Claire (Oxford: Oxford University Press, 2009)
Recent social and political changes have focused attention on the debate about the relationship between language and culture. This book offers an accessible survey of key concepts such as social context and cultural authenticity, using insights from fields which include linguistics, sociology and anthropology
Includes bibliographical references.
Keywords: Language and culture